Increased Levels of VEGF-A and HIF-1α in Turkish Children with Crimean-Congo Hemorrhagic Fever - Murat Sefikogullari; Ali Kaya; Huseyin Aydin; Enver Sancakdar; Veysel Kenan Celik; Gokhan Bagci (Tehran University of Medical Sciences, 2017)
Background: Crimean-Congo Hemorrhagic Fever (CCHF) is a disease characterized by serious course, including acute viral fever, ecchymosis, thrombocytopenia, liver dysfunction and high rate of mortality. Hypoxia Inducible Factor-1α (HIF-1α) and Vascular Endothelial Growth Factor-A (VEGF-A) play an important role both in the inflammatory process and plasma leakage. The aim of this study was to define HIF-1α and VEGF-A serum levels obtained from CCHF patients and control group and to investigate whether these factors were correlated with the pathogenesis of this disease. Methods: Thirty cases younger than 17 yr confirmed by RT-PCR and/or ELISA for CCHF were included in this study. Thirty age and sex matched healthy peoples were enrolled as controls. Blood samples collected from the patient and control groups. Serum levels of HIF-1α and VEGF-A were measured with ELISA. Results: Levels of HIF-1α and VEGF-A were statistically significantly increased in CCHF patients compared to the control group (P< 0.05).  A significant positive correlation was found between the levels of HIF-1α and VEGF-A in the patient group (P< 0.01). The levels of ALT, AST, CK, aPTT, WBC and Thrombocyte count were significantly higher in the patients than in the control group (P< 0.001). A positive correlation was found among the levels of AST and CK from biochemical parameters and VEGF and HIF-1α in the patient group (P< 0.05) Conclusion: HIF-1α and VEGF-A might play an important role in CCHF pathogenesis.